(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this paper, we suggested two new techniques for transforming multi-objective linear fractional programming problems into single-objective linear fractional programming problems (SOLFPP) and then solving them by methods of SOLFPP. Illustrative numerical examples are presented for demonstration purposes. Also, the obtained results are compared with another method studied previously.